A lesson from intravascular imaging: insights for recognizing a spontaneous coronary artery dissection - Buccheri, Dario; Milazzo, Diego; Geraci, Salvatore; Vaccaro, Giovanni; Caramanno, Giuseppe (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Spontaneous coronary artery dissection (SCAD) is still today an underdiagnosed disease due to the absence of angiographic hallmarks in more than 70% of cases. In several cases, an intravascular imaging is a sole tool for recognizing a dissection. Particularly, optical coherence tomography analysis (OCT) could represent the gold standard technique of easy interpretation and prompt diagnosis. Here we present a rare case of multivessel spontaneous coronary artery disease (SCAD) with atypical collateral circulation.